Characterization and structure‐guided engineering of the novel versatile terpene monooxygenase CYP109Q5 from Chondromyces apiculatus DSM436. Issue 2 (27th December 2018) - Klenk, Jan M.; Dubiel, Paulina; Sharma, Mahima; Grogan, Gideon; Hauer, Bernhard
Summary: One of the major challenges in chemical synthesis is the selective oxyfunctionalization of non‐activated C‐H bonds, which can be enabled by biocatalysis using cytochrome P450 monooxygenases. In this study, we report on the characterization of the versatile CYP109Q5 from Chondromyces apiculatus DSM436, which is able to functionalize a wide range of substrates (terpenes, steroids and drugs), including the ring of β‐ionone in non‐allylic positions. The crystal structure of CYP109Q5 revealed flexibility within the active site pocket that permitted the accommodation of bulky substrates, and enabled a structure‐guided approach to engineering the enzyme. Some variants of CYP109Q5 displayed a switch in selectivity towards the non‐allylic positions of β‐ionone, allowing the simultaneous production of 2‐ and 3‐hydroxy‐β‐ionone, which are chemically challenging to synthesize and are important precursors for carotenoid synthesis. An efficient whole‐cell system finally enabled the production of up to 0.5 g l −1 hydroxylated products of β‐ionone; this system can be applied to product identification in further biotransformations. Overall, CYP109Q5 proved to be highly evolvable and active. The studies in this work demonstrate that, using rational mutagenesis, the highly versatile CYP109Q5 generalist can be progressively evolved to be an industrially valuable specialist for the synthesis of specific products. Abstract : Here, we report on the identification, expression, biochemical and structural characterization as well as enzyme engineering of CYP109Q5 from the myxobacterium Chondromyces apiculatus DSM436. Overall, CYP109Q5 exhibits a versatile substrate spectra, high activities as E. coli whole‐cell biocatalyst and has shown to be highly evolvable. In addition, even non‐allylic positions of the norisoprenoid β‐ionone could be oxyfunctionalized. Thus, CYP109Q5 is highly interesting for future industrial applications.